Spitting images: remaking saliva as a promissory substance. Issue 2 (3rd April 2017) - Kragh-Furbo, Mette; Tutton, Richard
Abstract : Of the bodily substances in which STS scholars, anthropologists, sociologists, and medical historians have been interested, saliva has arguably been overlooked. Yet, in the past 20 years, saliva has become important to the development of consumer genetic tests. Historically, expectoration has been associated with the spread of disease and social indecency, but when the personal genomics company 23andMe began hosting spit parties in 2007, the act of spitting was transformed into an act of self-empowerment through which the individual gained new health information and saliva turned into a new biological source for measuring health and illness. Attending to saliva's social meanings over time, and by analyzing 23andMe "unboxing" YouTube videos, we argue that saliva has become a promissory substance whose place is no longer reserved only for the inner spaces of the body, but circulates outside the body, forming an important part of the contemporary bioeconomy.